(untitled) (Fiep Bulletin - online, 2013)
Objective: interpret the perceptions of the senile in a group of elderly people Campina Grande-PB on oral health. Methodology: exploratory-descriptive cross-sectional outline with a quantitative approach, developed with 80 subjects, applying a validated form and considering all the ethical aspects of research involving human beings. Results: showed that the higher proportion of elderly people perceived as excellent or good (68.7 %) oral healthcare, even all (100%) already having dental losses and 85% using dental prosthesis. Conclusion: the senile perceive their oral health in a unique way, because even with the high degree of dental loss and use of dental prostheses, there is satisfactoriness regarding their general perceptions.